Lepanthes florenciana (Orchidaceae: Pleurothallidinae), a new species from the Eastern Andes of Colombia - Moreno, Juan Sebastián; Hoyos, David; Rincón, Milton; Sierra-Ariza, Mario; Valencia Escalante, Maria Fernanda; Gutiérrez Morales, Nicolás (Phytotaxa, 2022)
A new species of Lepanthes from the Eastern Andes of Colombia is described and illustrated. Lepanthes florenciana is most similar to Lepanthes niphas, but it can be distinguished by the petals transversely trilobed with the upper and lower lobe dolabriform (vs. transversely bilobed with the lobes narrowly triangular), a lunate lip blades (vs. semi-orbicular) and an oblong pubescent appendix (vs. a minute apiculum in the sinus).